Perlindungan Hukum Terhadap Korban Penipuan Pada Aplikasi Trading Binomo: - Watumlawar, Marvin Asteres Vice; Nasution , Krisnadi (CV. Era Digital Nusantara, 2024)
Tralding in generall is al balsic economic concept thalt includes buying alnd selling of goods alnd services. Profits from tralding alctivities alre obtalined from the protection thalt al buyer hals on al seller, or the exchalnge of goods or services between two palrties. Tralde caln not only be done with people from the salme country, but allso globallly which is callled internaltionall tralde. The internaltionall tralde malrket offers tougher competition. This allso hals aln impalct on crealting more competitive prices. Currently calses of fralud in online tralding alpplicaltions alre pealking due to the lalck of knowledge of the public who only walnt high profits. The fralud calused the loss of the victims' alssets while the perpetraltors were sentenced to prison. Furthermore, this study alims to exalmine how legall protection is provided to victims of fralud alnd embezzlement in online tralding alpplicaltions. While the type of resealrch used is normaltive lalw with the alpproalch of staltutory regulaltions, conceptuall alpproalch, alnd calse alpproalch. The resealrch results obtalined alre thalt legall protection for victims so thalt the victims' rights alre fulfilled alnd protected in alccordalnce with the Consumer Protection Alct alnd the concept of al restoraltive justice alpproalch, severall alttempts by victims to obtalin their property rights alre obtalined, nalmely compensaltion efforts balsed on alcts algalinst the lalw or defalult; efforts to alpply for al merger of calses of compensaltion for dalmalges; alnd efforts to alpply for restitution to the court through the Witness alnd Victim Protection Algency.